Intima- media thickness of соmmоn carotid artery in patients with arterial hypertension and present or absent metabolic syndrome - G. Kh. Sharipova; M. A. Saidova; V. B. Mychka; T. V. Balakhonova; O. N. Vorobyeva; I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2008)
Aim: To study changes in intima-media thickness of common carotid artery (CCA IMT) in patients with arterial hypertension (AH) and present or absent metabolic syndrome (MS).Material and methods: The study included 303 patients with Stage I-III AH and MS, aged 25-70 years (mean age 52 ± 18 years); 110 men and 193 women. All patients were divided into 2 groups (AH+MS and АН-MS) by MS presence or absence, respectively. The groups were comparable by sex and age distribution. Pach group was also divided into three subgroups by AH stage (I-III). Pipid profile assessment, 24-hour blood pressure monitoring (BPM) and carotid artery ultrasound were performed in all patients.Results: CCA IMT was similar in participants with Stage I-II AH with or without MS. In Stage III AH, it was significantly higher among those with AH and MS, comparing to MS-free hypertensive individuals: 0,99+0,15 vs. 0,79+0,11 mm, respectively (p<0.05). AH duration correlated with mean CCA IMT (r=0,41, p<0.001), and IMT correlated with total cholesterol level in Stage III AH patients (r=0,42, p<0.01), low-density lipoprotein cholesterol (r=0,34, p<0,01), waist circumference (r=0,31, p<0.05), and blood glucose levels (r=0.29, p<0,01).Conclusion. In AH patients, CCA IMT was associated with Stage III AH, MS, age, AH duration, systolic and pulse BP levels.